Adesão e preservação do tratamento de diabetes tipo II : a relação das pessoas com o diabetes tipo II e os medicamentos - Palhas, Sergio Ricardo Duarte (2017)
This study aimed to know the beliefs that guide the attitudes regarding adherence and maintenance of treatment in people with type II diabetes, being used as methodological method the qualitative approach. Fourteen people with type II diabetes participated in the study, being used the in-depth interview as instrument of data collection and the technique of content analysis, thematic modality, for their drug treatment. Through the analysis, three themes of significance were found - The influence of the knowledge of type II diabetes and its consequences; Beliefs, treatments and the relationship between doctors and patients, and the role of the family, and society in relation to the person with type II diabetes. It was found that people with type II diabetes have a theoretical knowledge of the importance of taking medications correctly and according to prescriptions and medical guidelines, it was also verified that the family and the doctor are motivating factors for adherence to treatment.